2014
DOI: 10.1002/nau.22677
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management for female urinary incontinence and pelvic organ prolapse review 2013: Summary of the 5th International Consultation on Incontinence

Abstract: AimsThe objective of the 5th International Consultation on Incontinence (ICI) chapter on Adult Conservative Management was to review and summarize the new evidence on conservative management of urinary incontinence (UI) and pelvic organ prolapse (POP) in order to compile a current reference source for clinicians, health researchers, and service planners. In this paper, we present the review highlights and new evidence on female conservative management. MethodsRevision and updates of the 4th ICI Report using sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 42 publications
2
87
0
5
Order By: Relevance
“…Treatment of any aetiological factor may improve a woman's sexual function (SF). Pelvic floor muscle training (PFMT) is recommended as the first-line treatment for all types of UI and mild-moderate POP [9], and some studies have shown that successful treatment of UI or POP with PFMT also improves some aspects of a woman's sexual life and her SF [10][11][12][13][14][15], but this topic has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of any aetiological factor may improve a woman's sexual function (SF). Pelvic floor muscle training (PFMT) is recommended as the first-line treatment for all types of UI and mild-moderate POP [9], and some studies have shown that successful treatment of UI or POP with PFMT also improves some aspects of a woman's sexual life and her SF [10][11][12][13][14][15], but this topic has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on comparative effectiveness indicates that BT is either equivalent to or more effective than medications for reducing incontinence and OAB symptoms [11-20] but there is limited data for comparison of efficacy of BT and PFMT with or without biofeedback. Cochrane review published in 2014 supports the widespread recommendation that PFMT be included in first-line conservative management programs for women with stress and other types of urinary incontinence [21].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] These observations have led the 5th International Consultation on Incontinence to upgrade its recommendation for this modality. 26 In patients significantly bothered by their POP but who do not want surgery, and in those who are not medically fit or planning to become pregnant again, a pessary can be tried. These devices, usually made of silicone, come in a variety of shapes and sizes and are inserted in the vagina to reduce the prolapse by supporting the pelvic organs.…”
Section: Managementmentioning
confidence: 99%